SEKRETARIS PERUSAHAAN DAN PERAN PENYELENGGARAAN ADMINISTRASI - Aminudin Azis; eva mirza; Elya Zahra Aida F (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2022)
Secretarial administration means the entire process of implementing a series of structuring activities for office work and other assistance tasks, in order to support the smooth achievement of organizational goals. Secretarial administration has the objective of securing company secrets. The research method used is a qualitative descriptive research method using data collection techniques through interviews, observation, and documentation. Data processing techniques are carried out by presenting data related to the role of the corporate secretary as the organizer of secretarial administration at PT INKA Multi Solusi Madiun. The results obtained show that the corporate secretary has the role of organizing secretarial administration at PT INKA Multi Solusi Madiun in accordance with Gaol's theory (2015) covering five things. First, the recording of management activities, namely the recording of correspondence, guest books, disposition of incoming mail, internal document expeditions, telephone books. Second, implementing the administrative center, carrying out collection, recording, sending, duplicating, archiving activities. Third, as a corporate communication tool, the corporate secretary acts as an intermediary for conveying information. Fourth, executors who hold company secrets, use filing cabinets, filing cabinets, computers as media. Fifth, as a documentation center, recording, compiling, archiving important company files.